2016
DOI: 10.2807/1560-7917.es.2016.21.35.30331
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of H5N6, H7N9 and H9N2 avian influenza A viruses from air sampled at live poultry markets in China, 2014 and 2015

Abstract: Zoonotic infections by avian influenza viruses occur at the human–poultry interface, but the modes of transmission have not been fully investigated. We assessed the potential for airborne and fomite transmission at live poultry markets in Guangzhou city and in Hong Kong Special Administrative Region (SAR), China, during 2014 and 2015. Viral genome and infectious avian influenza A viruses of H5N6, H7N9, and H9N2 subtypes were detected predominantly from particles larger or equal to 1 μm in diameter in the air s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 34 publications
4
76
2
Order By: Relevance
“…The merits of bioaerosol sampling for respiratory viruses are coming to the forefront as researchers have used this approach to detect virus from air emitted by individuals with laboratory‐confirmed influenza, during severe acute respiratory syndrome coronavirus (SARS‐CoV) and Middle East respiratory syndrome coronavirus (MERS‐CoV) outbreaks, and to assess the environmental burden of avian influenza viruses in wet markets . In this study, we evaluated three portable samplers using artificial aerosols and a translational, in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…The merits of bioaerosol sampling for respiratory viruses are coming to the forefront as researchers have used this approach to detect virus from air emitted by individuals with laboratory‐confirmed influenza, during severe acute respiratory syndrome coronavirus (SARS‐CoV) and Middle East respiratory syndrome coronavirus (MERS‐CoV) outbreaks, and to assess the environmental burden of avian influenza viruses in wet markets . In this study, we evaluated three portable samplers using artificial aerosols and a translational, in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…Air was sampled weekly from a university campus in Hong Kong from October 2016 to June 2018 except during the summer holidays in 2017 (weeks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and on public holidays. Samples were collected from canteens, lecture halls, shuttle buses, and the University Health Service (UHS) during peak hours of human flow, using 6-13 air samplers per week.…”
Section: Air Sample Collectionmentioning
confidence: 99%
“…Using a library of barcoded viruses, Varble et al found that respiratory droplet transmission between ferrets involved only single-digit numbers of virions (Varble et al, 2014). Reports of A(H7N9) cases developing subsequent to patient visits to live bird markets despite lack of poultry contact, and the detection of virus in air sampled from such markets, indicate that zoonotic infection may also occur after human exposure to low quantities of aerosolized virus (Li et al, 2015;Liu et al, 2014;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%